2017
DOI: 10.1016/j.tem.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and β Adrenergic Receptor Signaling: Crosstalk in Heart

Abstract: Recent advances show that insulin may affect β adrenergic receptor (βAR) signaling in heart, to modulate cardiac function in clinically relevant states such as diabetes and heart failure. Conversely, activation of βAR regulates cardiac glucose uptake and promotes insulin resistance in HF. We discussed recent characterization on the interaction between cardiac insulin receptor and βAR in myocardium, in which insulin stimulation cross talk with cardiac βAR via insulin receptor substrate-dependent and G protein r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 92 publications
2
29
0
1
Order By: Relevance
“…The mechanisms of adrenoceptor activation, its downstream targets, its signal specificity versus bias and receptor dynamics have been extensively studied for understanding the role of adrenergic system in cardiovascular pathophysiology (Lohse, 2015). Also, the cross talk between adrenergic signaling and that by other receptor viz., insulin, EGF and TGFβ play a critical role in cardiovascular function (Saha et al, 2012;Heger et al, 2016;Fu et al, 2017;Mohan et al, 2017). Signaling by these receptors in heart involve a plethora of kinases, phosphatases, second messengers and gene regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of adrenoceptor activation, its downstream targets, its signal specificity versus bias and receptor dynamics have been extensively studied for understanding the role of adrenergic system in cardiovascular pathophysiology (Lohse, 2015). Also, the cross talk between adrenergic signaling and that by other receptor viz., insulin, EGF and TGFβ play a critical role in cardiovascular function (Saha et al, 2012;Heger et al, 2016;Fu et al, 2017;Mohan et al, 2017). Signaling by these receptors in heart involve a plethora of kinases, phosphatases, second messengers and gene regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the prevalence of diabetes is augmented in patients with HF and hyperglycemia/hyperinsulinemia can strongly contribute to the impairment of cardiac function as well as worsen prognosis ( Dei Cas et al, 2015 ; Jia et al, 2016 ; Komici et al, 2018 ). Furthermore, an insulin-resistant state (insulin resistance in both cardiac and peripheral tissues) seems to occur as a consequence of increased circulating CAs, in HF patients ( Paolisso et al, 1991 ; Shimizu et al, 2012 ; Fu et al, 2017 ). In this regard, it is not surprising that both HF and diabetic patients show SNS overactivity ( Lymperopoulos et al, 2013 ; Han et al, 2016 ).…”
Section: β-Adrenergic Signaling In Heart Failurementioning
confidence: 99%
“…In this regard, it is not surprising that both HF and diabetic patients show SNS overactivity ( Lymperopoulos et al, 2013 ; Han et al, 2016 ). The insulin receptor (Ins-R) and β-AR cross talk, share similar down-stream signaling components, such as G αi , β-arrestins and GRK2, and counter-regulate each other ( Song et al, 2001 ; Morisco et al, 2005 ; Cipolletta et al, 2009 ; Garcia-Guerra et al, 2010 ; Mangmool et al, 2016 ; Fu et al, 2017 ). This strict interaction was further clarified when a direct interaction in a membrane complex was found between Ins-R and β 2 -AR ( Mandić et al, 2014 ).…”
Section: β-Adrenergic Signaling In Heart Failurementioning
confidence: 99%
“…Insulin receptor substrates have multiple functions, including enzyme binding activity, insulin binding activity, and binding activity of insulin receptor substrates [46]. There are few studies on the involvement of Insr in Ab regulation.…”
Section: Pur-alpha Plays An Important Role In the Progression Of Alzhmentioning
confidence: 99%